Characterization of the Candiru Antigenic Complex (Bunyaviridae: Phlebovirus), a highly diverse and reassorting group of viruses affecting humans in tropical america - Palacios, Gustavo (2011)
The genus Phlebovirus of the family Bunyaviridae consists of approximately 70 named viruses, currently assigned to nine serocomplexes (species) based on antigenic similarities. Sixteen other named viruses that show little serologic relationship to the nine recognized groups are also classified as tentative species in the genus. In an effort to develop a more precise classification system for phleboviruses, we are attempting to sequence most of the named viruses in the genus with the goal of clarifying their phylogenetic relationships. In this report, we describe the serologic and phylogenetic relationships of 13 viruses that were found to be members of the Candiru serocomplex; 6 of them cause disease in humans. Analysis of full genome sequences revealed branching inconsistencies that suggest five reassortment events, all involving the M segment, and thus appear to be natural reassortants. This high rate of reassortment illustrates the inaccuracy of a classification system based solely on antigenic relationships.